Morte como desafio afetivo para o profissional da saúde: ansiedade e sentimentos de quem lida com o paciente terminal com câncer - Coelho, Daniella Antunes Pousa Faria (2008)
It is a Cross-sectional and multi-disciplinary study whose population selection was made by department of human resources (composed by a Manager, an Oncologist and a Psychologist) from the hospital where this research was realized. They also collaborated with important information about the work of that professionals in the hospital. We also counted on a Statistic who made study design calculating the sample and analyzing data. This research issued Evaluating health professionals anxiety levels who care for cancer terminally ill and their feelings about that work as well as identifying the factors which have influence on it. 100 health professionals from the Hospital which is a reference on cancer caring in Brazil situated in the city of Natal, state of Rio Grande do Norte, participated of this research. There was a sample loss of 21%. Data were collected through a questionnaire and State-Trait Anxiety Inventory (STAI). Results showed that 15% of the professionals have low State Anxiety levels, 70% Medium State Anxiety levels and 15% high State anxiety levels. The Number of Patients and Working in another Institution have interfered in the anxiety levels. Doctors and Nursing Assistants and Technicians have got the highest high State Anxiety percentage (25%). 73% of them declare to feel some sort of different behavior and/or feelings in caring for terminally ill. The most remarkable professionals feelings were Suffering and Sadness, and Terminally ill Children was the most difficult age group to care for. We conclude that work overload and having more than one job can interfere in professional stress levels and anxiety. Dealing with terminally ill, specially children one, can cause on the professionals psychological suffering. It s recommended the development of supporting and training strategies to reduce and/or to prevent Stress and Anxiety high levels